Bridging the perception gap? When top-down built megaprojects meet bottom-up perceptions: a case study of Suramadu bridge, Indonesia. Issue 1 (2nd January 2022) - Delphine,; Witte, Patrick; Spit, Tejo
ABSTRACT: For the last few decades, the development of mega-infrastructure projects has been high on the agendas of policymakers in Southeast Asia. Despite the potential benefits of such projects, there are also inevitable societal impacts that often lead to protests by local people. In general, most literature on megaprojects focuses solely on managing projects, with limited coverage of local people's perceptions. This article, however, offers an analytical approach to perception making, adopted from psychology theories, which is then elaborated upon in a quantitative and qualitative empirical setting using the Suramadu cable-stayed bridge in Indonesia as a case study. Our main argument is that perceptions about megaprojects can change as a result of long-term, high-level exposure to such projects. The results imply the need for megaproject development to take people's perceptions into account to bridge the gap between top-down expected benefits and bottom-up acceptance or rejection by those outside the central power.